Scientific Research II - Bunge, M. author. aut Link
VIII, 374 p. 2 illus.
Keywords: This volume is a logical sequel of Volume I, The Search for System: indeed, it concerns the ways theoretical systems are put to work and subjected to test. Yet it can be read independently by anyone familiar with some factual theories, referring back to Volume I when necessary. Special Symbols AS; B the set A is included in the set B AvB the union of the sets A and B AnB the common part of the sets A and B aEB the individual a is in (or belongs to) the set A Card (A) cardinality (numerosity) of the set A AxB Cartesian product of the sets A and B en(A) consequence(s) of the set A of assumptions equals by definition =dt definition Dt· some x (or there is at least one x such that) (3 x) e empirical datum e* translation of e into a semiempirical, semitheoreticallanguage h hypothesis m(r) measured value of the degree r m(; ) average (or mean) value of a set of measured values of ,; P-jT T presupposes P p, q arbitrary (unspecified) propositions (statements) P(x) x has the property P (or x is a P) {xl P(x)} set of the x such that every x is a P pVq p and/or q (inclusive disjunction) p &q p and q (conjunction) p-+q if p, then q (conditional or implication) p if and only if q (biconditional or equivalence) p-q sum over i 2:; t theorem, testable consequence.